Learning opportunities and learning behaviours of small business starters: Relations with goal achievement, skill development and satisfaction - Van Gelderen, Marco; Van der Sluis, Lidewey; Jansen, Paul (Springer, 2005)
Learning is a vital issue for small business starters, contributing to short term and long term business performance, as well as to personal development. This study investigates when and how small business starters learn. It specifies the situations that offer learning opportunities, as well as the learning behaviours that small business starters can employ in order to learn from these opportunities. In a cross-sectional, quantitative study of recently started small business founders, learning opportunities and learning behaviours are related to three outcome measures: a performance outcome (goal achievement), a personal growth outcome (skill development), and an affective evaluation outcome (satisfaction). The results show the importance of learning opportunities and learning behaviours in influencing these outcome variables, albeit not always in the directions we hypothesized.
Keywords: Learning; Learning opportunities; Learning behaviours; Entrepreneurship; Small business start-ups; Business performance; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management